Pregnancy outcomes in antiphospholipid antibody positive patients: prospective results from the AntiPhospholipid Syndrome Alliance for Clinical Trials and InternatiOnal Networking (APS ACTION) Clinical Database and Repository ('Registry'). Issue 1 (14th June 2022) - Erton, Zeynep Belce; Sevim, Ecem; de Jesús, Guilherme Ramires; Cervera, Ricard; Ji, Lanlan; Pengo, Vittorio; Ugarte, Amaia; Andrade, Danieli; Andreoli, Laura; Atsumi, Tatsuya; Fortin, Paul R; Gerosa, Maria; et al.
Abstract : Objectives: To describe the outcomes of pregnancies in antiphospholipid antibody (aPL)-positive patients since the inception of the AntiPhospholipid Syndrome Alliance for Clinical Trials and InternatiOnal Networking Registry. Methods: We identified persistently aPL-positive patients recorded as 'pregnant' during prospective follow-up, and defined 'aPL-related outcome' as a composite of: (1) Preterm live delivery (PTLD) at or before 37th week due to pre-eclampsia (PEC), eclampsia, small-for-gestational age (SGA) and/or placental insufficiency (PI); or (2) Otherwise unexplained fetal death after the 10th week of gestation. The primary objective was to describe the characteristics of patients with and without aPL-related composite outcomes based on their first observed pregnancies following registry recruitment. Results: Of the 55 first pregnancies observed after registry recruitment among nulliparous and multiparous participants, 15 (27%) resulted in early pregnancy loss <10 weeks gestation. Of the remaining 40 pregnancies: (1) 26 (65%) resulted in term live delivery (TLD), 4 (10%) in PTLD between 34.0 weeks and 36.6 weeks, 5 (12.5%) in PTLD before 34th week, and 5 (12.5%) in fetal death (two associated with genetic anomalies); and (2) The aPL-related composite outcome occurred in 9 (23%). One of 26 (4%) pregnancies with TLD, 3/4 (75%) with PTLD between 34.0 weeks and 36.6 weeks, and 3/5 (60%) with PTLD before 34th week were complicated with PEC, SGA and/or PI. Fifty of 55 (91%) pregnancies were in lupus anticoagulant positive subjects, as well as all pregnancies with aPL-related composite outcome. Conclusion: In our multicentre, international, aPL-positive cohort, of 55 first pregnancies observed prospectively, 15 (27%) were complicated by early pregnancy loss. Of the remaining 40 pregnancies, composite pregnancy morbidity was observed in 9 (23%) pregnancies.